INFLAMMATORY BOWEL DISEASE AND ASSOCIATED CARDIOVASCULAR DISEASE OUTCOMES: A SYSTEMATIC REVIEW. (26th January 2023) - Naz, Sidra; Butey, Swatika; Jaiswal, Vikash; Dagar, Mehak; Huang, Helen; Ea Chia, Jia; Endurance, Evbayekha O; Raj, Nishchita; Patel, Srushti; Maroo, Dipansha; Mukherjee, Dattatreya; Hanif, Muhammad
Abstract: BACKGROUND: There is limited and conflicting data available regarding the Cardiovascular disease outcomes associated with Inflammatory Bowel Disease (IBD) OBJECTIVE: We aim to perform a systematic review to evaluate the cardiovascular outcomes and mortality associated with IBD patients. METHODS: A systematic literature search has been performed on PubMed, Embase, Cochrane, and Scopus from inception till May 2022 without any language restrictions. RESULTS: A total of 2, 029, 941 patients were included into the analysis from 16 studies. The mean age of the patients was 45.6 years. More females were found compared with males (57% vs 43%). The most common risk factors for Cardiovascular disease (CVD) included smoking (24.19%) and alcohol (4.60%). The most common co-morbidities included hypertension (30%), diabetes mellitus (14.41%), dyslipidemia (18.42%), previous CVD (22%), and renal disease (10%). Among outcomes All-cause mortality among IBD patients was 1.66%; Ulcerative Colitis (UC): 15.92%; and Crohn's disease (CD): 0.30%. Myocardial Infarction (MI) among IBD patients were 1.47%, among UC: 30.96%; and among CD: 34.14%. Cardiovascular Death (CVD) events among IBD patients were 1.95%. Heart failure events among IBD patients were 5.49%, while Stroke events among IBD Patients were 0.95%; among UC: 2.63%; and CD: 2.41% respectively. CONCLUSION: There was a possible association between IBD patients and adverse cardiovascular outcomes especially in young and females. Though there remains a lack of concrete treatment algorithms and assessment parameters that better characterize IBD risk factors, nutritional modifications and physical activity should be at the fore-front of CVD prevention in IBD.